2019
DOI: 10.3390/en12122410
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modeling and Structural Optimization of a Bistable Electromagnetic Vibration Energy Harvester

Abstract: A novel bistable electromagnetic vibration energy harvester (BEMH) is constructed and optimized in this study, based on a nonlinear system consisting mainly of a flexible membrane and a magnetic spring. A large-amplitude transverse vibration equation of the system is established with the general nonlinear geometry and magnetic force. Firstly, the mathematical model, considering the higher-order nonlinearities given by nonlinear Galerkin method, is applied to a membrane with a co-axial magnet mass and magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…When the linear speed becomes lower at the ends of the stroke, the generator stops generating power. Therefore, the existing solutions have a low-power output [ 33 ]. A possible solution by which to improve energy harvesting efficiency in the case of low-speed electric machines with permanent magnets is decreasing the pole period [ 34 ].…”
Section: The Conceptmentioning
confidence: 99%
“…When the linear speed becomes lower at the ends of the stroke, the generator stops generating power. Therefore, the existing solutions have a low-power output [ 33 ]. A possible solution by which to improve energy harvesting efficiency in the case of low-speed electric machines with permanent magnets is decreasing the pole period [ 34 ].…”
Section: The Conceptmentioning
confidence: 99%
“…Membrane’s response to steady vibration was obtained and it was concluded that the proposed model is capable of harvesting vibrational energy in a broader bandwidth at lower frequencies and how membrane thickness exhibit enhancement on the output power. 18 In Ostrowski et al, 19 a non-linear EMEH that encapsulates displacement amplifier and spring bumpers were presented. The purpose of using mechanical amplifier was to improve overall performance of EMEH for the same level of base excitation.…”
Section: Introductionmentioning
confidence: 99%
“…Anjum and He [32] used the variational iterative method combined with Laplace transform to find the approximate nonlinear frequency of a switch oscillatory system. Zhang et al [33] established the low-order vibration equation of the flexible thin-film electromagnetic actuator via nonlinear Galerkin method, and optimized the structural parameters to achieve a large output power. Herisanu et al [34] utilized the optimal auxiliary functions method (OAFM) to obtain exact and approximate analytical solutions of the model in an asymmetric electromagnetic actuator near the primary resonance.…”
Section: Introductionmentioning
confidence: 99%